The Paradox of High Achievement: When an Outstanding EFL Student Struggled to Graduate on Time - Elisa Ratih (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
High-achieving students are commonly associated with strong academic performance and timely graduation. However, not all academically successful students are able to complete their studies without obstacles. This study explores the experiences of an outstanding English as a Foreign Language (EFL) pre-service teacher who struggled to graduate on time despite her remarkable academic achievements. Employing narrative inquiry, this study investigates the participant’s lived experiences, focusing on the factors contributing to her delayed graduation. The findings reveal that financial difficulties, problematic academic supervision, and mental health challenges significantly influenced the participant’s demotivation and prolonged study completion. These challenges also affected her motivation, social life, academic productivity, and emotional well-being. Despite these obstacles, the participant gradually regained motivation through personal support systems and self-driven strategies. This study highlights that academic achievement does not necessarily protect students from educational and psychological struggles. The findings contribute to broader discussions on student well-being, academic support, and higher education completion among high-achieving EFL students.